2017
DOI: 10.1016/j.aott.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the hip rotation centre from landmarks in pelvic radiograph

Abstract: ObjectiveThe hip rotation centre (HRC) is an important reference point in cases of total hip arthroplasty (THA). The aim of this study is to investigate the reference points in the Turkish population that enable the identification of the HRC in standard pelvic radiographs.MethodsThe pelvic radiographs of 50 women and 50 men were examined. The mean age was 46.2 (range; 18–91). Patients with deformity of the hip joint and non-standard pelvic radiograph due to hip flexion contracture were excluded from the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
3
0
4
Order By: Relevance
“…Previous literature has suggested that the HJC and pelvic height ratios do vary and are dependent on sex [19,20]. Interestingly, Bombaci et al [42] studied the pelvic radiographs of 100 men and women, where they measured the distance between the HJC to the teardrop (HRC-TD) and a line tangent to the ischial tuberosities (HRC-TI) and the pelvic height. In their study, males had greater pelvic heights, HRC-TI, and HRC-TD measurements than females on average.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has suggested that the HJC and pelvic height ratios do vary and are dependent on sex [19,20]. Interestingly, Bombaci et al [42] studied the pelvic radiographs of 100 men and women, where they measured the distance between the HJC to the teardrop (HRC-TD) and a line tangent to the ischial tuberosities (HRC-TI) and the pelvic height. In their study, males had greater pelvic heights, HRC-TI, and HRC-TD measurements than females on average.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,17 En la actualidad se ha desarrollado un método aplicado a la población turca que ha demostrado ser sencillo y reproducible. 1,2 Nuestro estudio es el primero del que tenemos conocimiento en el que se establecen las bases antropométricas del centro de rotación de la cadera en la población mexicana utilizando una población homogénea, multicéntrica y en un número suficiente para ser estadísticamente significativo. Al analizar las mediciones realizadas en esta población descubrimos que existen variaciones entre las medidas antropométricas de la población turca y la nuestra que deben tomarse en consideración una vez que se planifique la ATC, por lo tanto nos dimos a la tarea de definir porcentajes específicos para nuestra población para poder hacer uso del método de Bombaci (RH-CRC de 16% en hombres y mujeres y RV-CRC de 30% en hombres y 29% mujeres).…”
Section: Discussionunclassified
“…(AP) determinada por la distancia entre las líneas interisquiáticas (LIs) e interiliaca (LIi) y un porcentaje (30% en hombres y 29% en mujeres) de esta altura hacia vertical de la LIs, relación vertical al centro de rotación de la cadera (RV-CRC) y un porcentaje de la AP hacia horizontal (14% en hombres y 13% en mujeres) de la lágrima de Kohler, relación horizontal al centro de rotación de la cadera (RH-CRC), hasta el momento sólo validado en población turca. 2,9 Debido a que está bien descrito que la morfología de la pelvis y cadera, y por lo tanto sus puntos de referencia pueden variar significativamente entre poblaciones, el propósito de este estudio es conocer si el método de Bombaci para obtener el CRC en otras poblaciones también es aplicable a la población mexicana.…”
Section: Level Of Evidence: IIIunclassified
See 1 more Smart Citation
“…В основе других методик лежало использование математических уравнений регрессии, полученных в ходе многочисленных измерений обзорных рентгенограмм таза пациентов разного пола, возраста и даже расовой принадлежности [13,14,15,16]. В качестве горизонтальных референтных линий обычно применялись параллельные, соединяющие вершины подвздошных гребней и седалищных бугров или основания «фигур слезы» и каудальные точки крестцово-подвздошных сочленений.…”
unclassified